An inverse stage‐shift model to estimate the excess mortality and health economic impact of delayed access to cancer services due to the COVID‐19 pandemic. Issue 4 (10th February 2021) - Degeling, Koen; Baxter, Nancy N.; Emery, Jon; Jenkins, Mark A.; Franchini, Fanny; Gibbs, Peter; Mann, G. Bruce; McArthur, Grant; Solomon, Benjamin J.; IJzerman, Maarten J.
Abstract: Aim: Decreased cancer incidence and reported changes to clinical management indicate that the COVID‐19 pandemic has delayed cancer diagnosis and treatment. This study aimed to develop and apply a flexible model to estimate the impact of delayed diagnosis and treatment on survival outcomes and healthcare costs based on a shift in the disease stage at treatment initiation. Methods: A model was developed and made publicly available to estimate population‐level health economic outcomes by extrapolating and weighing stage‐specific outcomes by the distribution of stages at treatment initiation. It was applied to estimate the impact of 3‐ and 6‐month delays based on Australian data for stage I breast cancer, colorectal cancer, and lung cancer patients, and for T1 melanoma. Two approaches were explored to estimate stage shifts following a delay: (a) based on the relation between time to treatment initiation and overall survival (breast, colorectal, and lung cancer), and (b) based on the tumor growth rate (melanoma). Results: Using a conservative once‐off 3‐month delay and considering only shifts from stage I/T1 to stage II/T2, 88 excess deaths and $12 million excess healthcare costs were predicted in Australia over 5 years for all patients diagnosed in 2020. For a 6‐month delay, excess mortality and healthcare costs were 349 deaths and $46 million over 5 years. Conclusions: The health and economic impacts of delays in treatment initiation cause an imminent policy concern. More accurate individual patient data on shifts in stage of disease during and after the COVID‐19 pandemic are critical for further analyses. Abstract : Presentation and application of a framework to estimate the long‐term impact of delayed cancer diagnoses and treatment due to the COVID‐19 pandemic. Over the next 5 years, nearly 90 excess deaths and $12 million excess healthcare costs for 4 common cancers in Australia were estimated based on conservative assumptions.